Peracetic acid as a single endodontic irrigant: effects on microhardness, roughness and erosion of root canal dentin - Keine, Kátia C. [UNESP]; Kuga, Milton C. [UNESP]; Coaguila-Llerena, Hernán [UNESP]; Palma-Dibb, Regina G.; Faria, Gisele [UNESP] (Wiley, 2020)
The aim was to assess the effects of 1% peracetic acid (PAA) as a single endodontic irrigant on microhardness, roughness, and erosion of root canal dentin, compared with 2.5% sodium hypochlorite (NaOCl) and with 2.5% NaOCl combined with 17% EDTA. Forty human, single-rooted tooth hemisections were submitted to Knoop microhardness test, before and after the following irrigation protocols: PAA = 1% PAA; NaOCl = 2.5% NaOCl; NaOCl-EDTA-NaOCl = 2.5% NaOCl +17% EDTA +2.5% NaOCl; and SS = saline. Another 40 roots were instrumented, irrigated with the same protocols, and sectioned longitudinally. The roughness analysis was performed on the mesial section using a confocal laser scanning microscope, whereas erosion was analyzed on each third of the distal section, using a scanning electron microscope. The data were analyzed using ANOVA and Tukey post-tests, and Kruskal-Wallis and Dunn post-tests (α =.05). The PAA and NaOCl-EDTA-NaOCl groups showed no significant differences (p >.05); both promoted reduction in microhardness and increase in roughness, compared with the NaOCl and SS groups (p <.05). NaOCl-EDTA-NaOCl promoted higher erosion in the cervical and middle thirds than the other groups (p <.05); there was no difference among PAA, NaOCl, and SS (p >.05). There was also no difference among the groups regarding the apical third (p >.05). PAA used as a single endodontic irrigant caused reduction in root canal dentin microhardness and increase in roughness in a similar way to NaOCl-EDTA-NaOCl; however, PAA caused less erosion than NaOCl-EDTA-NaOCl.
Keywords: erosion; microhardness; peracetic acid; roughness; sodium hypochlorite